1D Co‐Pi Modified BiVO4/ZnO Junction Cascade for Efficient Photoelectrochemical Water Cleavage. Issue 10 (20th March 2014) - Moniz, Savio J. A.; Zhu, Jun; Tang, Junwang
<x xml:space="preserve">Abstract</x> The most important factors dominating solar hydrogen synthesis efficiency include light absorption, charge separation and transport, and surface chemical reactions (charge utilization). In order to tackle these factors, an ordered 1D junction cascade photoelectrode for water splitting, grown via a simple low‐cost solution‐based process and consisting of nanoparticulate BiVO4 on 1D ZnO rods with cobalt phosphate (Co‐Pi) on the surface is synthesized. Flat‐band measurements reveal the feasibility of charge transfer from BiVO4 to ZnO, supported by PL measurements and photocurrent observation in the presence of an efficient hole scavenger, which demonstrate that quenching of luminescence of BiVO4 and enhanced current are caused by electron transfer from BiVO4 to ZnO. A dramatic cathodic shift in onset potential under both visible and full arc irradiation, coupled with a 12‐fold increase in photocurrent (ca. 3 mA cm‐2) are observed compared to BiVO4, resulting in ≈47% IPCE at 410 nm (4% for BiVO4) with high solar energy conversion efficiency (0.88%). The reasons for these enhancements stem from enhanced light absorption and trapping, in situ rectifying electron transfer from BiVO4 to ZnO, hole transfer to Co‐Pi for water oxidation, and facilitating electron transport along 1D ZnO.